Analytical solution for unsteady second grade fluid in presence of non-coaxial rotation - Ismail, Zulkhibri; Mohamad, Ahmad Qushairi; Mohd Zin, Nor Athirah; Lim, Yeou Jiann; Shafie, Sharidan; Khan, Ilyas (Institute of Physics Publishing, 2017)
The analytical solution of non-coaxial rotation for second grade fluid is discussed in this paper. The effect of heat and mass transfer through an oscillating vertical disk is also been considered. The Laplace transform technique is used to obtain the solution of velocity, temperature and concentration profiles. The velocity profiles are obtained in two parts of velocity, there are primary and secondary velocities. All pertinent parameters that involved in these profiles are plotted and analyzed graphically. It is found that, the primary velocity first decreases and then increases whereas the secondary velocity is only increased by increasing second grade parameter. From the observation, the primary velocity is higher compared to the secondary velocity for all parameter studied. The solutions of this problem are satisfied the initial and boundary conditions.